Fresno County Young Lawyers Hopper Luncheon Keynoter California Supreme Court Associate Justice Malcolm Lucas - Watkins, Howard::::::::: (1985)
Presiding Justice George Brown at lectern introducing Justice Lucas; Lucas and Jim Christiansen seated at head table